Understanding Perceptions of Political Science Students on Islamic Content from Political Figures: Implications for Choosing Leaders in the 2024 Election - Nasya Putri Fadilla; Ratna Nur Azizah; Diny Nurafnie; Zahra Nurhaliza Insani (Higher Education Spiritual Pedagogies, 2023)
The 2024 election is one of the hot topics discussed by Indonesian people from all walks of life. Not only limited to conversations among middle-aged people, this election has also become a hot issue in conversation among young people, especially students. The purpose of this study is to find out the purpose and impact of creating Islamic content by political figures according to the views of political students, to find out the perspectives of Political Science students on Islamic content from political figures on social media, and to find out what criteria need to be considered for a Muslim to choose a leader. A leader is defined as someone who is able to influence and persuade other parties to carry out orders or actions to achieve common goals. The method used in this research is a qualitative method with a descriptive approach and is implemented by conducting interviews with informants. Making Islamic content on social media by political figures is not always followed by a negative connotation because if the creation of Islamic content is not associated with political interests, it can be a quite relevant tool for Indonesian people, especially Muslims, to be able to understand Islamic topics presented through the medium. more casual. To choose a leader is not only seen from showing an image in a content along with an interesting topic, but also needs to be in accordance with the criteria for selecting a leader in Islam, therefore as a society we must be wise in receiving and obtaining information.